(untitled) (Colombia Medica, 1987)
The risk factor for postcesarean section infection in an epidemiological survey of "cases and controls" was studied in reviewing the clinical records of patients submitted to operation between January 1st and December 31st, 1984. From a total of 2596 cesarean sections, 99 patients had evidence of infection. They were compared with 142 controls taken randomly from a group of patients in the postcesarean period of the same procedure without evidence of postoperative infection. No significant differences (0.05) were seen in variables such as age, duration of operation, weeks of pregnancy, rupture of fetal membranes, and surgeon experience. The number of pregnancies and previous cesarean sections were significant (P > 0.05). An infection rate of 3.8% was found, a figure considered acceptable for this type of surgery classified as "clean-contaminated."